Opioid use and social disadvantage in patients with chronic musculoskeletal pain. Issue 3 (3rd May 2021) - Cheng, Abby L.; Brady, Brian K.; Bradley, Ethan C.; Calfee, Ryan P.; Klesges, Lisa M.; Colditz, Graham A.; Prather, Heidi
Abstract: Background: Historically, marginalized patients were prescribed less opioid medication than affluent, white patients. However, because of persistent differential access to nonopioid pain treatments, this direction of disparity in opioid prescribing may have reversed. Objective: To compare social disadvantage and health in patients with chronic pain who were managed with versus without chronic opioid therapy. It was hypothesized that patients routinely prescribed opioids would be more likely to live in socially disadvantaged communities and report worse health. Design: Cross‐sectional analysis of a retrospective cohort defined from medical records from 2000 to 2019. Setting: Single tertiary safety net medical center. Patients: Adult patients with chronic musculoskeletal pain who were managed longitudinally by a physiatric group practice from at least 2011 to 2015 ( n = 1173), subgrouped by chronic (≥4 years) adherent opioid usage ( n = 356) versus no chronic opioid usage ( n = 817). Intervention: Not applicable. Main Outcome Measures: The primary outcome was the unadjusted between‐group difference in social disadvantage, defined by living in the worst national quartile of the Area Deprivation Index (ADI). An adjusted effect size was also calculated using logistic regression, with age, sex, race, and Patient‐Reported Outcomes Measurement Information System (PROMIS) Pain Interference and Physical Function scores as covariates. Secondary outcomes included adjusted differences in health by chronic opioid use (measured by PROMIS). Results: Patients managed with chronic opioid therapy were more likely to live in a zip code within the most socially disadvantaged national quartile (34.9%; 95% confidence interval [CI] 29.9–39.9%; vs. 24.9%; 95% CI 21.9–28.0%; P < .001), and social disadvantage was independently associated with chronic opioid use (odds ratio [OR] 1.01 per ADI percentile [1.01–1.02]). Opioid use was also associated with meaningfully worse PROMIS Depression (3.8 points [2.4–5.1]), Anxiety (3.0 [1.4–4.5]), and Pain Interference (2.6 [1.7–3.5]) scores. Conclusions: Patients prescribed chronic opioid treatment were more likely to live in socially disadvantaged neighborhoods, and chronic opioid use was independently associated with worse behavioral health. Improving access to multidisciplinary, nonopioid treatments for chronic pain may be key to successfully overcoming the opioid crisis.